2021
DOI: 10.21203/rs.3.rs-155394/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increased Resistance of SARS-CoV-2 Variants B.1.351 and B.1.1.7 to Antibody Neutralization

Abstract: The Covid-19 pandemic has ravaged the globe, and its causative agent, SARS-CoV-2, continues to rage. Prospects of ending this pandemic rest on the development of effective interventions. Two monoclonal antibody (mAb) therapeutics have received emergency use authorization, and more are in the pipeline. Furthermore, multiple vaccine constructs have shown promise, including two with ~95% protective efficacy against Covid-19. However, these interventions were directed toward the initial SARS-CoV-2 that emerged… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 22 publications
4
73
0
2
Order By: Relevance
“…Sera from mRNA-1273 vaccinated NHP or human sera was shown to have 6-8 fold reduced neutralizing activity against the B.1.351 variant SARS-CoV-2 in several assessments, although the level of neutralization remained at levels that are predicted to be protective. 26,39 Results in this study, however, showed that after the primary series of mRNA-1273, only a 2-fold reduced neutralization against the B.1.351 virus was evident 2 weeks after the second dose. A 6.6-fold reduction was seen at day 212, more relevant to what has been measured from human sera.…”
Section: Discussionsupporting
(Expert classified)
“…Sera from mRNA-1273 vaccinated NHP or human sera was shown to have 6-8 fold reduced neutralizing activity against the B.1.351 variant SARS-CoV-2 in several assessments, although the level of neutralization remained at levels that are predicted to be protective. 26,39 Results in this study, however, showed that after the primary series of mRNA-1273, only a 2-fold reduced neutralization against the B.1.351 virus was evident 2 weeks after the second dose. A 6.6-fold reduction was seen at day 212, more relevant to what has been measured from human sera.…”
Section: Discussionsupporting
(Expert classified)
“…Shortly after the first Wuhan Hu-1 (WA-1) genome sequence was published ( 2 ), spike proteins were generated for use in spike-specific antibody discovery ( 3 – 5 ). Recently, virus variants first detected in the UK (e.g., B.1.1.7)( 6 ), South Africa (e.g., B.1.351) ( 7 ) and Brazil (P.1) ( 8,9 ) have been shown to contain mutations that mediate resistance to therapeutic monoclonal antibodies, have increased transmissibility and to potentially increase pathogenicity ( 10 – 14 ). Additionally, vaccines designed based on the original WA-1 outbreak strain sequence elicit antibody responses that show decreased in vitro neutralizing activity against variants ( 1416 ).…”
Section: Main Textmentioning
confidence: 99%
“…Recently, virus variants first detected in the UK (e.g., B.1.1.7)( 6 ), South Africa (e.g., B.1.351) ( 7 ) and Brazil (P.1) ( 8,9 ) have been shown to contain mutations that mediate resistance to therapeutic monoclonal antibodies, have increased transmissibility and to potentially increase pathogenicity ( 10 – 14 ). Additionally, vaccines designed based on the original WA-1 outbreak strain sequence elicit antibody responses that show decreased in vitro neutralizing activity against variants ( 1416 ). In this study, we investigated antibodies isolated from convalescent subjects who were infected by the WA-1 strain during the first few months of the outbreak, determined their reactivity against variants of concern (VOCs) and defined the structural features of their binding to spike.…”
Section: Main Textmentioning
confidence: 99%
“…The isolation of RBD-specific cross-reactive mAbs neutralizing SARS-CoV-2 and SARS-CoV suggests that RBD-based vaccines could in principle elicit Abs that neutralize distantly related sarbecoviruses 18,19,53 . RBD-based vaccines are also unaffected by S mutations outside of the RBD, especially in the highly variable N-terminal domain (NTD) 37,54–59 . Here, we explored dose-sparing strategies for the RBD-NP vaccine and evaluated the impact of genetic diversity among SARS-CoV-2 clinical isolates and sarbecoviruses on vaccine-elicited Ab responses.…”
Section: Introductionmentioning
confidence: 99%